A Full-Scale Combined Anaerobic-Aerobic System for Treatment of Melamine Formaldehyde Wastewater - Lai, Aloysius Min Yun (1999)
The objective of this full scale study is to determine the effectiveness of the combined two stage anaerobic-aerobic processes to treat high strength melamine formaldehyde (MF) wastewater at ambient temperature. The raw wastewater with COD concentration of between 25,000 to 50,000 ppm at normal operating condition. Two stage physical/chemical treatment processes were carried out in this experiment to ensure consistent wastewater stream to be treated at the downstream anaerobic BioFil and aerobic system. The two BioFil reactors total combined volume of 70.0 m3 (35 MT each) and the Aeration Tank has a capacity of 5.0 m3 to cater for a flow rate of 15-25 Concentration of biomass was achieved through entrapment in the macrostructure of cosmo (HDPE) balls used in the BioFil reactors. Hydraulic retention time (HRT) for BioFil was controlled by centrifugal pump at 24, 18, 12 and 6 hours with corresponding organic loading of 2.4, 4.8, 9.7 and 38.8 kg COD/m3/day. Under steady state condition, the highest percentage removal achieved was COD 86.3%, BOD 87.0%, TSS 84.4% and 86.8% for VSS at HRT 24 hours. Generally the BioFil was able to stabilized at a period of 5 to 8 days when a new loading rate was applied. Accordingly, the HRT for Aeration Tank (AT) was 8, 6 and 4 hours with substrate loading of 13.9, 55.4 and 1 45.2 kg COD/m3/day. Under steady state condition in AT, the highest percentage removal of organic matter was observed at HRT 8 hours, with COD 86.2%, BOD 86.5%, 80.2% and 86.0% for TSS and VSS respectively. The cosmo balls used in the BioFil proven to be an effective carrier material which functioned as a separation device thus limiting biomass being washed out. The combined anaerobic-aerobic system is a suitable process to treat high strength wastewater. Based on this full scale study, higher efficiency of this system can be anticipated if longer HRT is allowed in the Aeration Tank.